Art : a crash course - Freeman, Julian, 1950- (New York : Watson-Guptill, 1998)
"Art - A Crash Course is designed for the armchair aficionado with artistic longings, those of us who know what we like but can't put a name on it. It's a briskly written fact-packed history of Western art with all the tedious research done for you, techniques explained in foolproof terms, and a handy timeline. Read this and you will never again confuse your impressionists with your expressionists, your fresco with your mural, or your Millais with your Millet. And you can open your mouth with confidence, as Art a Crash Course contains a unique pronunciation guide."--BOOK JACKET.
Includes index.
Keywords: Art -- History